Fiscal competition for imperfectly-mobile labor and capital : a comparative dynamic analysis - David E. Wildasin (Center for Economic Studies and ifo Institute (CESifo), 2009)
Interjurisdictional flows of imperfectly-mobile migrants, investment, and other productive resources result in the costly dynamic adjustment of resource stocks. This paper investigates the comparative dynamics of adjustment to changes in local fiscal policy with two imperfectly mobile productive resources. The intertemporal adjustments for both resources depend on complementarity/substitutability in production and the adjustment cost technologies for each, implying that the evaluation of the fiscal treatment of one resource must account for the simultaneous adjustment of both.
Keywords: B23; H22; H71; H87; J61; 330; fiscal competition; labor mobility; capital mobility; comparative dynamics; Kommunale Finanzpolitik; Institutioneller Wettbewerb; Steuerwettbewerb; Arbeitsmobilität; Internationale Kapitalmobilität; Regionaler Finanzmarkt; Anpassungskosten; Dynamisches Modell; Theorie